PENGARUH MOTIVASI BELAJAR TERHADAPKEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IV MI NURUL ULUM MADIUN - Avita Febri Hidayana (Jurnal Paradigma, 2022)
Mathematics is a subject that many students do not like, and students motivation is still relatively low to participate in learning mathematics in class. The success of the teaching and learning process is influenced by many factors, one of which is learning motivation. Motivation of a person can do what makes them happy and will encourage them to do something. Motivation is also an urge to do something, motivation can arise from oneself as well as from the encouragement of others. In this study, researchers used quantitative methods. The purpose of this study was to determine whether there is an effect of learning motivation on the ability to understand mathematical concepts of fourth grade students at Nurul Ulum Sidorejo Madiun Elementary Islamic School. The data collection techniques used questionnaires and tests. The population of this research is the fourth grade students of Elementary Islamic School Madiun totaling 22 students. For the data analysis technique using Simple Linear Regression assisted by SPSS 16.0 program. Based on calculations at a significance level of 5%, it shows that there is an influence of learning motivation on students' ability to understand mathematical concepts by 40.8% or sufficient effect while the rest is influenced by other variables.